ENHANCING EDUCATIONAL OPPORTUNITIES: THE IMPACT OF MAMUN UNIVERSITY IN UZBEKISTAN (International Educators Conference, 2025)
This paper discusses the role of Mamun University in improvement of education in Uzbekistan. It addresses the goals of the university, the target development, and many other benefits extended to the students such as scholarship, employment opportunities, career guidance and many more. Furthermore, the paper brings to the fore the role played by Mamun University in the education system by launching new ideas and academic research as well as advancing values of national culture through its specific environment existed in Khorezm. By focusing on the activities and accomplishments of the university, it helps to understand the university’s contribution to the reform of higher education in Uzbekistan and the training of students for the international environment.